Biochemical and Biological Bases of Resistance in Solanaceous Vegetables Against Bacterial Wilt Incited By Ralstonia Solanacearum (Smith) Yabuuchi et al - Sheela Paul T (Department of Plant Pathology, College of Horticulture, 1998)
An investigation on biochemical, biological and nutritional bases of resistance in solanaceous vegetables against bacterial wi1t incited by Ralstonia solanacearum (Smith) Yabuuchi et al., has been attempted. The pathogen R. solanacearumwas isolated from respecti ve hosts and characterised by various morphological, cultural, biochemical and physiological tests upto biovar level. The three isolates were cross inoculable, and were sensitive to AmDistryn and Streptocycline. Based on these studies the tomato and chilli isolates were identified as Ralstonia solanacearum race I biovar III and that from brinjal as R. solanacearum race I biovar V. The study on toxigenic property of the bacterial isolates revealed that the toxic metabolites were not host specific. Out of the 43 varieties / lines screened , 12 varieties / lines were selected, one each from resistant, moderately resistant, moderately susceptible and susceptible